PENERAPAN MODEL AKTIVE LEARNING UNTUK MENINGKATKAN HASIL BELAJAR PAI SISWA KELAS V SDN 04 TANJUANG HARO - Irmawanti Irmawanti; Zulfani Sesmiarni; Rodi; Masyitah Shellyni (Jurnal Ilmu Pendidikan dan Kearifan Lokal, 2024)
Study Action Class This aiming For increase results Study Islamic Religious Education through application of the active learning model on student Class V at SDN 04 Tanjuang Haro . As for background behind study This is results Study part big student on eye PAI lessons show low yield or be under standard minimum competency . This is due to by low level involvement student in the learning process , as well domination method less lecture interesting interest Study students . Research This use PTK design implemented in four cycle , where every cycle consists of from stage planning results observation , implementation , observation , and reflection . Subject study is 14 students Class V of SDN 04 Tanjuang Haro . Data collected covering to activity learning And results assessment beginning And end . Results study show that the application of the active learning model can increase results students learning Islamic Religious Education class V of SDN 04 Tanjung Haro . On cycle I, average value student experience improvement compared to with Pre Cycle , namely about 50 % of students reach minimum completion . On cycle II, improvement results Study student around 71.43 % . At cycle III, improvement results Study student around 92.86 %. Apart from that , the result observation show that student more motivated And involved active in the learning process that uses the active learning model . With Thus , it can concluded that the active learning model is effective in increase results Study Islamic Religious Education in student Class V of SDN 04 Tanjuang Haro.